PENGARUH BERAS HITAM TERHADAP KADAR GULA DARAH PADA PASIEN DIABETES MELITUS TIPE II DI DUSUN KADIROJO II, SLEMAN, YOGYAKARTA - Istiarini, Chatarina Hatri (Jurnal Kesehatan, 2017)
Background: Diabetes Melitus (DM) is a chronic condition with the indication of blood glucose that exceeds normal level (Perkeni, an Association of Indonesian Endocrinology, 2016). Indonesia is now at the forth rank after US, China and India. It is estimated that in 2020 Indonesian citizens above 20 with diabetes will be 178 million with an assumsion of DM prevalence of 4.6% will be 8.2 million (Perkeni, 2016). Objective: To investigate the influence of black rice toward blood glucose in DM clients type II. Method: It was a Pre-Experimental research with one-group pretest-posttest. T-test analysis was applied to investigate its mean differences between blood glucose level before and after having black rice in DM clients type II of Kadirojo II. Result: The result shows that p val: 0,013, it means smaller than ?: 0,05.Conclusion: There is an influence of black rice toward blood glucose in DM clients type II in Kadirojo II, Sleman, Yogyakarta in August 2016. Suggestion: DM clients type II in Kadirojo II are suggested to consume black rice as an alternative of low glocose but high fiber carbohydrate; the local government is suggested to socialize the benefit of black rice to control blood glucose level.